Economic- financial viability of an agroforestry system in Pará-Brazil: A case study in Concórdia do Pará (Research, Society and Development, 2022)
With the growth of movements that value products from sustainable systems, there was an expansion of agricultural and forestry production associated with environmental preservation, one of them is the Agroforestry Systems (SAF) that associate trees with agricultural and/or animal species. In this sense, this article aimed to analyze the implementation of SAF in a productive rural area in the municipality of Concórdia do Pará, in Pará. The study was developed in a private area of a rural farmer, using a quantitative approach and descriptive method, supported by a semi-structured interview in which aspects such as technical production coefficients, input prices, investments such as agricultural implements, labor and other production factors were analyzed. The data obtained in the interview served to identify the production cost, revenues and the operational cash flow (FCO) of SAF, which provided the basis for obtaining feasibility indicators such as Net Present Value of R$ 120,257.20, Internal Rate of Return of 248 % p.a., Benefit/Cost Ratio of R$1.91 and Payback Time of two years. The results show that the project is economically viable, and the balance in the FCO becomes positive from the second year of the project, with the sale of cassava and passion fruit flour. Finally, a study of this nature helps rural producers to better manage their SAF and consequently increase their profitability.